A Mild, General, Metal‐Free Method for Desulfurization of Thiols and Disulfides Induced by Visible‐Light. Issue 5 (28th April 2021) - Qiu, Wenting; Shi, Shuai; Li, Ruining; Lin, Xianfeng; Rao, Liangming; Sun, Zhankui
Main observation and conclusion: A visible‐light‐induced metal‐free desulfurization method for thiols and disulfides has been explored. This radical desulfurization features mild conditions, robustness, and excellent functionality compatibility. It was successfully applied not only to the desulfurization of small molecules, but also to peptides. Abstract :